Combined transcriptomic and metabolomic analysis of the mechanism by which Bacillus velezensis induces resistance to anthracnose in walnut - Wang, Linmin; Zhu, Tianhui (Frontiers in Microbiology, 2024)
Walnut (Juglans spp.), a significant deciduous tree of economic and ecological importance, 12 faces substantial threats from walnut anthracnose, primarily caused by Colletotrichum gloeosporioides. 13 Bacillus velezensis has shown promise in mitigating this fungal pathogen. To delve deeper into the 14 induction mechanism of B. velezensis on walnut plant resistance, we conducted a metabolomic anal-15 ysis on walnut leaves from six different treatment groups. Specifically, the groups were defined as 16 follows: Group B.v. was inoculated with B. velezensis alone, Group CK served as the blank control, 17 and Group C.g. was inoculated solely with C. gloeosporioides. Group B.v.-C.g. received B. velezensis 18 followed by C. gloeosporioides inoculation. Group B.v.+C.g. underwent simultaneous inoculation 19 with both B. velezensis and C. gloeosporioides, while Group C.g.-B.v. was treated first with C. gloeo-20 sporioides then B. velezensis. A total of 1503 metabolites were detected, mainly including flavonoids, 21 terpenoids, and steroids. The results revealed that B. velezensis spraying not only enhanced the in-22 herent resistance of walnut plants but also significantly regulated walnut plants already infected 23 with C. gloeosporioides. This was mainly achieved by inducing walnut plants to adjust their metabolic 24 pathways such as salicylic acid, jasmonic acid, and abscisic acid, thereby strengthening their stress 25 response. Transcriptomic and metabolomic correlation analyses showed that in the comparisons of 26 B.v. vs. CK, C.g. vs. CK, and C.g.-B.v. vs. C.g., 59, 244, and 122 differential abundance metabolites 27 were detected, along with 7860, 3677, and 5587 differential genes, respectively. Amino acid synthesis, 28 starch and sucrose metabolism, photosynthesis, phenylpropane metabolism, purine metabolism, 29 and glutathione metabolism played crucial roles in walnut's disease resistance mechanism. Further 30 analysis revealed that B. velezensis induced walnut plants to regulate multiple genes, such as 31 LOC109005403, LOC108985444 and LOC118344177 , resulting in the production of defensive metab- olites such as palmitic acid, coumarin and ferulic acid , thereby enhancing their resistance to C. gloeosporioides.